Silver sulfadiazine nanosuspension-loaded thermosensitive hydrogel as a topical antibacterial agent - Liu X (Dove Medical Press, 2018)
Xiaoya Liu, Hui Gan, Chaoran Hu, Wenzhong Sun, Xiaoxia Zhu, Zhiyun Meng, Ruolan Gu, Zhuona Wu, Guifang Dou Department of Pharmaceutical Sciences, Beijing Institute of Radiation Medicine, Beijing 100850, People’s Republic of China Background: Silver sulfadiazine (AgSD) is widely employed as an antibacterial agent for surface burn management. However, the antibacterial activity of AgSD was restrained because of the lower drug solubility and possible cytotoxicity. Objective: This study aimed to formulate stable silver sulfadiazine/nanosuspensions (AgSD/NSs) with improved AgSD solubility and prepare a suitable carrier for AgSD/NS delivery. Nanotechnology was used to overcome the low drug dissolution rate of AgSD, while the new carrier loaded with AgSD/NS was assumed to decrease the possible cytotoxicity, enhance antibacterial activity, and promote wound healing. Methods: AgSD/NSs were prepared by high pressure homogenization method. Poloxamer 407-based thermoresponsive hydrogels were prepared by cold method as carriers of AgSD/NS to obtain AgSD/NS-loaded thermoresponsive hydrogel. Scanning electron microscope (SEM), Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) were used to measure the physicalchemical properties of AgSD/NSs and AgSD/NS-loaded gel. The cytotoxicity of the AgSD/NS-loaded gel was evaluated using methyl thiazolyltetrazolium assay with L929 mouse fibroblast cell lines. In vitro antibacterial activities of AgSD/NSs and AgSD/NS loaded gel were also measured. Results: Stable AgSD/NSs with an average particle size of 369 nm were formulated while 1.5% P407 was selected as a stabilizer. The optimized AgSD/NS thermoresponsive hydrogel exhibited the gelation temperature of approximately 30°C. A significant improvement in solubility was observed for AgSD nanoparticles (96.7%) compared with AgSD coarse powders (12.5%). The results of FTIR and XRD revealed that the physicochemical properties of AgSD/NS were reserved after incorporating into the hydrogel. The cell viability after incubation with AgSD/NS-loaded thermoresponsive hydrogel improved from 60.7% to 90.6% compared with incubation with AgSD/NS directly. Drug release profiles from the thermoresponsive hydrogel increased compared with the commercial AgSD cream, implying less application frequency of AgSD cream clinically. In vitro antibacterial studies manifested that AgSD nanocrystallization significantly enhanced the antibacterial activity compared with the AgSD coarse powder. Conclusion: The combination of AgSD nanosuspensions and thermoresponsive hydrogel effectively improved the AgSD antibacterial activity and decreased the cytotoxicity. This study also suggested that a poloxamer thermoresponsive hydrogel could be used as a delivery system for other nanocrystals to decrease possible nanotoxicity. Keywords: cytotoxicity, wound healing infection, nanotechnology